Ժամանակի ընկալումը Ը.—Ժ. դարերի հայ եկեղեցական մատենագրութեան մէջ - Շիրինեան, Արուսեակ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Период VIII—X веков представляет собой важный этап переосмысления категории времени в духовной традиции: от космологического и исторического её понимания к ритуальному, онтологическому и сотериологическому. В это время наблюдается постепенный переход от восприятия времени как внешней последовательности исторических событий к осмыслению его как формы внутреннего духовного становления личности. Теология времени всё меньше опирается на хронологические и причинно-исторические схемы и всё больше раскрывается в горизонте символа, молитвенного опыта и обожения. Если в предыдущие века, особенно в V—VII вв., представление о времени сохраняло черты античного мировоззрения — как о течении сотворённых, направляемых и контролируемых Богом событий,— то в сочинениях христианских авторов VIII—X вв. акцент постепенно смещается: время начинает осмысляться как вну- треннее движение души к Богу. Под влиянием восточно-христианского мистицизма, включающего элементы неоплатонической мысли, всё более отчётливо проявляется идея теозиса — приобщения человека к нетварной божественной жизни через участие в таинствах и в сакральном, ритуальном времени. В VIII веке особое значение приобретают такие выдающиеся представители армянской богословской и духовной традиции, как Степанос Сюнеци, Ован Одзнеци и Хосровик Переводчик, чьи труды оказали существенное влияние на формирование богословия, обрядовой поэзии и церковной культуры того времени. The period from the eighth to the tenth centuries represents a crucial stage in the re-evaluation of the category of time within the spiritual tradition: a shift from its cosmological and historical understanding toward a ritual, ontological, and soteriological one. During this time, we observe a gradual transition from perceiving time as an external sequence of historical events to interpreting it as a form of inner spiritual development of the person. The theology of time becomes less dependent on chronological and causal-historical schemes and increasingly unfolds within the horizon of symbol, prayerful experience, and deification. If in previous centuries, particularly in the fifth to seventh centuries, the concept of time retained features of the ancient worldview — as a flow of created events directed and governed by divine providence — then in the writings of Christian authors of the eighth to tenth centuries the emphasis gradually shifted: time began to be understood as the inner movement of the soul toward God. Under the influence of Eastern Christian mysticism, which incorporates elements of Neoplatonic thought, the idea of theosis—the participation of the human being in the uncreated divine life through engagement in the sacraments and in sacred, ritual time—became increasingly apparent. In the eighth century, particular significance was acquired by such outstanding representatives of the Armenian theological and spiritual tradition as Stepanos Syunetsi, Hovhan Odznetsi, and Khosrovik the Translator, whose works exerted a substantial influence on the formation of theology, liturgical poetry, and the ecclesial culture of that period.
Keywords: Կրօնագիտութիւն